Lady Kahhal, First Female Ophthalmologist and Medical Journalist in Iran: - Daneshfard, Babak; Golshani, Alireza; Foruzani, Abolghasem; Ghafouri, Ziba; Dalfardi, Behnam (Galen Medical Journal, 2015)
With the advent of constitutional revolution in Iran and the increase in people’s knowledge, women’s status changed and ultimately improved. Publishing newspaper was one of the women’s attempts to keep their rights. Lady Somayyeh Kahhal was the first woman in this field, as well as ophthalmology in Iran. She published the first specialized newspaper for women in Iran under the title of Danesh (Knowledge). Lady Kahhal tried to disseminate information on women’s rights, moral issues and also health and hygiene in her weekly-published newspaper. In this paper, we will review the remaining biographical information about Kahhal and will introduce her newspaper, Danesh. [GMJ.2015;4(2):129-32]